Bamboo Craft Business Development Strategy In Bangli District - Kartika, I Made; Amrita, Nyoman Dwika Ayu; Sedana, I Dewa Gede Putra; Herlambang, Putu Gede Denny (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
Bangli Regency is one of the centers for bamboo craft businesses in Bali Province. The bamboo craft products produced are keben, rice baskets, capil, bamboo bags, sokasi, and other woven materials made from bamboo. This research aims to determine the existence of craftsmen, their advantages and disadvantages as well as strategies that can be applied for business development. This research method uses descriptive to obtain an overview of business existence using IE (internal and external) matrix for effort to develop bamboo craft businesses in Bangli Regency. Based on the results of data collection, it is known that the total value of the IFE matrix owned by craftsmen is 3.47 and the total value of the EFE matrix is 3.15. This score is in the first cell of the IE matrix which means growth and development. There are three alternative strategies that can be implemented by craftsmen in developing their business, namely: 1). Market penetration; 2). Market development or expansion; and 3). Product development. Based on the QSPM results, market development or expansion had the highest Total Attractive Score (TAS) score, so it was selected as the most recommended strategy.